2015
DOI: 10.1371/journal.pone.0133876
|View full text |Cite
|
Sign up to set email alerts
|

Functional Role of NRF2 in Cervical Carcinogenesis

Abstract: Nuclear factor erythroid-2-related factor 2 (NFE2L2) is a transcription factor associated with resistance to chemotherapy and increased tumor growth. NRF2 is repressed by the inhibitor Keap1. The Keap1-NRF2 pathway is dysfunctional in multiple tumor types. Among Uighur women, the incidence of cervical squamous cell carcinoma (CSCC) and cervical intraepithelial neoplasia (CIN) was associated with elevated nuclear expression of NRF2 and decreased cytoplasmic expression of Keap1. Up-regulation of nuclear NRF2 was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 30 publications
3
47
0
Order By: Relevance
“…Emerging evidences suggest that when autophagy is impaired, p62 accumulates in the cytosol and tends to competitively bind with Keap1, a negative regulator of Nrf2, resulting in prolonged Nrf2 activation, 40 , 41 , 42 and that dysregulation of Nrf2 signaling pathway is able to promote cell proliferation and chemoresistance in several cancers. 43 , 44 , 45 , 46 In this study, we observed an autophagic flux and nuclear translocation of Nrf2 in the cells treated with ESI ( Figures 2 , 3 , 4 and 5 ). Moreover, knockdown of Nrf2 significantly attenuated the ESI-induced autophagy, whereas blockade of the autophagy with specific inhibitor 3-MA could not affect the ESI-induced Nrf2 activation ( Figure 6 ).…”
Section: Discussionsupporting
confidence: 59%
“…Emerging evidences suggest that when autophagy is impaired, p62 accumulates in the cytosol and tends to competitively bind with Keap1, a negative regulator of Nrf2, resulting in prolonged Nrf2 activation, 40 , 41 , 42 and that dysregulation of Nrf2 signaling pathway is able to promote cell proliferation and chemoresistance in several cancers. 43 , 44 , 45 , 46 In this study, we observed an autophagic flux and nuclear translocation of Nrf2 in the cells treated with ESI ( Figures 2 , 3 , 4 and 5 ). Moreover, knockdown of Nrf2 significantly attenuated the ESI-induced autophagy, whereas blockade of the autophagy with specific inhibitor 3-MA could not affect the ESI-induced Nrf2 activation ( Figure 6 ).…”
Section: Discussionsupporting
confidence: 59%
“…Immunofluorescence staining of Nrf2 in embryos at various developmental stages (from two-cell to morula stage) revealed that Nrf2 primarily accumulated in the cytoplasm, consistent with the reports of a previous study showing Nrf2 accumulation in the cytoplasm of endometrial glandular cells [ 22 ]. The expression pattern encouraged us to further investigate the possible roles of Nrf2.The knockdown of Nrf2 expression was shown to inhibit proliferation by inducing apoptosis in various cancer cells, and Nrf2 overexpression resulted in converse phenotypes [ 23 , 24 ]. However, little is known about the role of Nrf2 in early mouse embryo.…”
Section: Discussionmentioning
confidence: 99%
“…The expression Nrf2z in nuclear increases proliferation, promotes DNA replication, represses apoptosis and enhances migration and invasion in SiHa cells, a human cervical squamous cell carcinoma cell line, whereas Effects of Nrf2 silencing is opposite. 116…”
Section: Human Papillomavirus (Hpv)mentioning
confidence: 99%